Sources of free sugar in the diet of Saudi children - Mumena, Walaa Abdullah; Kutbi, Hebah Alawi (Frontiers in Public Health, 2024)
Data concerning sources of free sugar in the diet of Saudi children are limited. Identification of the top sources of free sugar would permit to develop tailored interventions that aid in meeting the recommendations of the World Health Organization for free sugar (≤ 25 g/day). This study aimed to investigate sources of free sugar in children's diet. A cross-sectional data of healthy children ages 6-12 years who reside in Saudi Arabia were collected from their mothers using online platforms (WhatsApp, Facebook, and X) (n=424; 210 boys and 214 girls). A phone interview was conducted with the mother and her child to collect data pertaining free sugar intake using a validated food frequency questionnaire that was specifically designed to assess free sugar intake among Saudi children. The primary sources of free sugar were Sweetened Beverages, followed by Sugars, Sweet Bakery Products, Other Desserts, and Candies, of which the added sugar consisted mostly of its total sugar. Children's intake of free sugar from solid food sources for the highest quartile almost doubled the amount of free sugar coming from liquid sources. Compared to boys, girls in the top quartile of free sugar intake consumed significantly higher amounts of solid sugars (p= 0.030). Only the intake of free sugar coming from Sweetened Beverages was associated negatively with age of children (p= 0.032). Public health interventions should emphasize the necessity of reducing the consumption of the top sources of free sugar to practically achieve the recommendations of free sugar intake.Supported by the latest evidence, the World Health Organization (WHO) announced a new guideline in 2015 targeting free sugars, recommending children and adults to limit the daily consumption of free sugar to < 10% of total energy, with a further reduction to < 5% or 25 g per day for additional Deleted: Department of 40 Deleted: P.O. Box 80215,